Is There a Correlation Between the Breast FibroglandularTissue Thickness Ratio and Mastalgia Severity in Patientswith Cyclic Mastalgia? - Erkuş, Figen; Bozdağ, Ahmet; Birkan, Zülfü; Demirkazik, Figen Basaran (My University, 2021)
Objective: The purpose of this study is to evaluate correlation between the breast fibroglandulartissue thickness ratio and mastalgia severity in patients with cyclic mastalgia. Materials and Methods: Ninety-six women with mastalgia in premenopausal reproductive agewere prospectively evaluated. All patients were evaluated by the same general surgeon andseverity of mastalgia was assessed by using visual analogue scale (VAS). Breast fibroglandulartissue thickness ratio was defined as the ratio of fibroglandular tissue thickness to distancebetween skin and anterior chest wall muscles. These measurements were made in the periareolarareas in the upper-outer quadrants of both breasts with ultrasound. Pearson correlation coefficienttest was used for statistical analysis. Results: The patients’ ages were between 18 and 39 with a mean age of 30.1. The meanfibroglandular tissue thickness ratio of the whole group was 0.618 mm. The Pearson’s coefficient rvalue for the correlation between the mean breast fibroglandular tissue ratio and VAS scores was0.791, which means that there is strong correlation. While we categorized patients in 3 groups ashaving mild, moderate and severe mastalgia The Pearson’s coefficient r value for correlationbetween the mean breast fibroglandular tissue ratio and severity groups is 0.737. Conclusion: In our study we found that the mean breast fibroglandular tissue ratio is stronglycorrelated with mastalgia severity in patients with cyclic mastalgia. A more effective analgesictreatment approach and a more careful follow-up in terms of cancer should be applied to patientswith high breast density.
Keywords: Dermatoloji; Genel ve Dahili Tıp